2020
DOI: 10.7150/jca.37006
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Urinary Long Non-coding RNAs Differentiate Bladder Cancer from Urocystitis

Abstract: Liquid biopsy is becoming a promising method for non-invasive cancer detection. In several proof-of-concept studies, long non-coding RNAs (lncRNAs) were found to be potential biomarkers for bladder cancer detection. The objective of this study was to discover a panel of cell-free, urinary lncRNAs as liquid biopsy biomarkers to non-invasively differentiate bladder cancer from chronic urocystitis. To this end, we collected urine samples from both bladder cancer patients and urocystitis patients. These samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The cycling parameters for miRNA were as follows: 95 °C for 30 sec, followed by 40 cycles of 95 °C for 5 sec and 60 °C for 30 sec. Finally, we quantified the miRNA level by using the ΔCt method that was previously described [37][38][39] . In short, the miRNA level = 2^ ΔCt multiplying 1000, where ΔCt was the difference between Ct value of the miRNA of interest to Ct value of internal controls.…”
Section: Samples and Clinical Characteristics This Study Was Conductmentioning
confidence: 99%
“…The cycling parameters for miRNA were as follows: 95 °C for 30 sec, followed by 40 cycles of 95 °C for 5 sec and 60 °C for 30 sec. Finally, we quantified the miRNA level by using the ΔCt method that was previously described [37][38][39] . In short, the miRNA level = 2^ ΔCt multiplying 1000, where ΔCt was the difference between Ct value of the miRNA of interest to Ct value of internal controls.…”
Section: Samples and Clinical Characteristics This Study Was Conductmentioning
confidence: 99%
“…Early differential diagnosis of cancer and precancerous lesions is an important method to decrease the risk of recurrence and improve prognosis (121). A study has demonstrated that the combination of UCA1, HOX transcript antisense intergenic RNA, hydatidiform mole associated and imprinted and metastasis-associated lung adenocarcinoma transcript 1 can distinguish between patients with bladder cancer and patients with urocystitis, with a sensitivity and specificity of 95.7% and 94.3%, respectively (121). Collectively, these findings suggest that it is feasible to use UCA1 as a diagnostic biomarker.…”
Section: Clinical Applications Of Uca1mentioning
confidence: 99%
“…The results are very heterogeneous, but promising candidate nucleic acids biomarkers have been identified with higher sensitivities and specificities than plasma ctDNA. The major studies that have investigated the role of exosomes in the diagnosis of BC are compiled in Table 3 [86,[97][98][99][100][101][102][103][104]. Although the specific functional role of exosomes in BC heterogeneity remains unclear, exosomes have emerged as potential noninvasive disease biomarkers with potential clinical significance.…”
Section: Circulating Mirnas and Othersmentioning
confidence: 99%
“…An alternative strategy to understand tumor heterogeneity might be liquid biopsy, which can detect genetic alterations and tumor cells present in peripheral blood or urine of patients with BC [105,99]. Peripheral blood-or urine-based genomic analyses were flexible in processing, and there are no specific device required for isolation, which have the potential to diagnose and dynamically monitor BC recurrence [82,78,106,69,65,79].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%